Implementasi Praktik Pekerja Sosial dalam Pemberdayaan Berbasis Edukasi Terkait Kekerasan Seksual Anak - Agustin, Nabila; Saputra, Reynaldi Yasir; Lubis, Arif Abdillah; Siregar, Hairani (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
Sexual violence against children in Indonesia is in the first position with the highest number of cases since 2019-2024. This needs to be a special concern for every party, including social workers. Therefore, in an effort to help prevent sexual violence against children, an education-based empowerment was carried out for grade 6 children at SDN 105275 using the social worker practice method. Among them are through the preparation stage, namely the unification of perceptions of each team member regarding the problems and groups to be empowered, the 2nd stage of assessment, namely identifying problems directly with the principal of SDN 105275, the 3rd stage of planning, namely preparing a design related to the empowerment program to be carried out, the 4th stage of program implementation, namely implementing empowerment programs through education related to the prevention and handling of sexual violence, and the last is the evaluation and termination stage, at this stage the results of the empowerment that has been carried out are seen. Then the results of empowerment are found, namely the increase in children's knowledge related to the prevention and handling of sexual violence which can be seen from the results of the post-test given, namely there is a comparison of the number of correct and incorrect answers which is quite a lot from the results of the pre-test conducted previously